2005
DOI: 10.1021/bi0508690
|View full text |Cite
|
Sign up to set email alerts
|

Anticooperativity in a Glu−Lys−Glu Salt Bridge Triplet in an Isolated α-Helical Peptide

Abstract: Phosphorylation is ubiquitous in control of protein activity, yet its effects on protein structure are poorly understood. Here we investigate the effect of serine phosphorylation in the interior of an α-helix when a salt bridge is present between the phosphate group and a positively charged side chain (in this case lysine) at i,i + 4 spacing. The stabilization of the helix is considerable and can overcome the intrinsically low preference of phosphoserine for the interior of the helix. The effect is pH dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 61 publications
(77 reference statements)
3
39
0
Order By: Relevance
“…7). Other simultaneous salt bridges (X → E(−4) & E(+4) and X → E(−3) & E(+3), for X = K or R) were not significantly populated, in agreement with the experimental finding of non-cooperativity in an alanine-based peptide with a K → E(−4) & E(+4) triplet pattern18. Glu residues are also able to form simultaneous salt bridges with two Lys or Arg partners (Supplementary Table S4).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…7). Other simultaneous salt bridges (X → E(−4) & E(+4) and X → E(−3) & E(+3), for X = K or R) were not significantly populated, in agreement with the experimental finding of non-cooperativity in an alanine-based peptide with a K → E(−4) & E(+4) triplet pattern18. Glu residues are also able to form simultaneous salt bridges with two Lys or Arg partners (Supplementary Table S4).…”
Section: Resultssupporting
confidence: 86%
“…Single E–K or E–R pairs of this type are known to promote the folding of monomeric α-helices in short (<20 residue) alanine-based peptides1516, and thus are assumed to stabilize long SAHs. Studies on short peptides have additionally suggested that K → E(+4) pairs are more helix-stabilizing than the reversed E → K(+4) orientation17, resolving previous conflicting reports161819. However, the equivalent study for E–R pairs is lacking.…”
mentioning
confidence: 98%
“…It has been known for some time that particular sequences of amino acids may have significant roles in protein folding and stability (Nagano, 1973;Nagano, 1974) and, more recent studies have shown how these patterns in pairs in β-sheets, (Fooks et al, 2006) loop sequences, (Crasto and Feng, 2001) particular (i, i + 4) pairs with helix-stabilizing effects (Andrew et al, 2001;Andrew et al, 2002;Butterfield et al, 2002) and dipole-affecting triplets (Iqbalsyah and Doig, 2005a;Olson et al, 2001) may have a stabilizing or destabilizing influence.…”
Section: Introductionmentioning
confidence: 99%
“…In particular for α-helices, these effects are consequence of several types of interactions between amino acid side chains -including aromatic interactions, (Butterfield et al, 2002;Meurisse et al, 2004;Thomas et al, 2002a;Thomas et al, 2002b) nonpolar/polar interactions, (Andrew et al, 2001) surface salt bridges (Iqbalsyah and Doig, 2005a;Olson et al, 2001) -and may be dependent on the relative positioning of the intervening side-chains. There is also the possibility of interactions between amino acid residue side chains and the α-helix backbone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation